Role of SrtA in Pathogenicity of Staphylococcus lugdunensis - Muzaffar Hussain; Christian Kohler; Karsten Becker (Microorganisms, 2020)
Among coagulase-negative staphylococci (CoNS), Staphylococcus lugdunensis has a special position as causative agent of aggressive courses of infectious endocarditis (IE) more reminiscent of IEs caused by Staphylococcus aureus than those by CoNS. To initiate colonization and invasion, bacterial cell surface proteins are required; however, only little is known about adhesion of S. lugdunensis to biotic surfaces. Cell surface proteins containing the LPXTG anchor motif are covalently attached to the cell wall by sortases. Here, we report the functionality of Staphylococcus lugdunensis sortase A (SrtA) to link LPXTG substrates to the cell wall. To determine the role of SrtA dependent surface proteins in biofilm formation and binding eukaryotic cells, we generated SrtA-deficient mutants (ΔsrtA). These mutants formed a smaller amount of biofilm and bound less to immobilized fibronectin, fibrinogen, and vitronectin. Furthermore, SrtA absence affected the gene expression of two different adhesins on transcription level. Surprisingly, we found no decreased adherence and invasion in human cell lines, probably caused by the upregulation of further adhesins in ΔsrtA mutant strains. In conclusion, the functionality of S. lugdunensis SrtA in anchoring LPXTG substrates to the cell wall let us define it as the pathogen’s housekeeping sortase.